2019
DOI: 10.23891/efdyyu.2019.163
|View full text |Cite
|
Sign up to set email alerts
|

Beşinci Sınıf Öğrencilerinin Çarpma ve Bölme İşlemine Yönelik Kurdukları Problemlerin Analizi

Abstract: Öz: Bu çalışmanın amacı ortaokul beşinci sınıf öğrencilerinin çarpma ve bölme işlemine yönelik kurdukları problemlerin ve bu işlemlere yükledikleri anlamların özelliklerini ortaya çıkarmaktır. Çalışmanın araştırma grubunu 2017-2018 eğitim öğretim yılında, Türkiye'nin * Bu araştırmanın bir kısmı 27. Uluslararası Eğitim Bilimleri Kongresi'nde sözlü bildiri olarak sunulmuştur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…Similarly, in the study of Ngah et al (2016), it was determined that most of the students posed simple problems. Other studies also point out that there are more problems with the exercise style of the tasks posed by the students (Crespo & Sinclair, 2008;Doruk & Doruk, 2019;Stickles, 2006). While it was found that most of the participants offered the correct solutions to the problems they posed in the free and semi-structured tasks, it was also found that there were errors in the solutions to the problems that were posed incorrectly or incompletely.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in the study of Ngah et al (2016), it was determined that most of the students posed simple problems. Other studies also point out that there are more problems with the exercise style of the tasks posed by the students (Crespo & Sinclair, 2008;Doruk & Doruk, 2019;Stickles, 2006). While it was found that most of the participants offered the correct solutions to the problems they posed in the free and semi-structured tasks, it was also found that there were errors in the solutions to the problems that were posed incorrectly or incompletely.…”
Section: Resultsmentioning
confidence: 99%
“…Bu durum bazı öğrencilerin yüzdeler konusunu gerçek hayatla ilişkilendirme konusunda güçlük yaşadığı anlamına gelebilir. Öğrencilerin kurdukları problemlerde alıştırma özelliğindeki problemlerin fazlalığı yapılan diğer çalışmalarda da göze çarpmaktadır (Crespo ve Sinclair, 2008;Doruk ve Doruk, 2019;Stickles, 2006). Etkinliklere alıştırma tarzında cevap veren öğrencilerin serbest problem kurma türündeki etkinliklerde ders kitaplarında ve diğer kaynaklarda yer alan, sıklıkla karşılaşılan türden problemler kurdukları görülmüştür.…”
Section: Sonuç Tartışma Ve öNerilerunclassified
“…Problem kurma yaklaşımı ile ilgili yapılan çalışmalar incelendiğinde bu çalışmaların geniş bir yelpazede yer aldığı görülmektedir. Bu çalışmalardan çoğunluğu öğrenci ve öğretmen adaylarının farklı konu alanlarında kurdukları problemlerin analiz edilmesine yöneliktir (Arıkan & Ünal, 2013;Çomarlı, 2018;Doruk & Doruk, 2019;Onkun Özgür, 2018;Sayı, 2018;Tekin Sitrava & Işık, 2018). Kimi çalışmalarda ise problem kurma becerisi ölçülmeye ve değerlendirilmeye çalışılmış (Akkan vd., 2009;Bayram, 2019;Dede & Yaman, 2005;Karaaslan, 2018;Korkmaz & Gür, 2006;Salman, 2012), kimi çalışmalarda da kurulan problemlerin matematiksel olarak doğru olup olmadığı araştırılmıştır (Akay vd., 2006;Aydoğdu & Türnüklü, 2019;English, 1998;Silver & Cai, 1996).…”
Section: Introductionunclassified
“…The majority of the studies on problem posing have been conducted to analyze the problems that student and teacher candidates have posed in different subject areas (Arıkan & Ünal, 2013;Çomarlı, 2018;Doruk & Doruk, 2019;Onkun Özgür, 2018;Sayı, 2018;Tekin Sitrava & Işık, 2018 ), to measure and evaluate their problem posing skills (Akkan, Çakıroğlu, & Güven, 2009;Bayram, 2019;Dede & Yaman, 2005;Korkmaz & Gür, 2006;Salman, 2012), to determine whether the problems they have posed are mathematically correct or not (Akay, Soybaş, & Argün, 2006;Aydoğdu & Türnüklü, 2019;English, 1998;Silver & Cai, 1996) and to reveal how they make sense of mathematical concepts in the problems they have posed and the difficulties they have experienced (Işık & Kar, 2012;Özdemir Yıldız, 2019;Toluk-Uçar, 2009). "Although there are so many studies on problem posing, no studies conducted about problem posing-based mathematics teaching at primary level have been encountered.…”
mentioning
confidence: 99%
“…Division is the most difficult and complex arithmetical operation to teach and learn among the four operations in terms of semantic structures (Kouba, 1989) comprehending both its meaning (Steffe, 1988), operation technique (Bağdat, 2020;Doruk & Doruk, 2019) and requiring preliminary knowledge such as multiplication (Kaasila, Pehkonen, & Hellinen, 2010). There are many reasons for its difficulty and complexity: (1) the lack of knowledge about the partitioning and measurement meanings of division is one of the primary reasons for students' difficulties with division (Doğan-Coşkun & Ev-Çimen, 2019a), (2) insufficient understanding of the functions of the divisor, dividend, quotient, and remainder in division as well as their relationships with one another (Correa, Nunes, & Bryant, 1988;Squire & Bryant, 2002;Doğan-Coşkun & Ev-Çimen, 2019a), (3) requiring good estimation skills and (4) inadequate consideration of the meanings of quotative and partitive division (Anghileri, Beishuizen, & van Putten, 2002).…”
mentioning
confidence: 99%